Promising domestic raw materials for use in meat products - Galenko, Oleg; Shapovalov, Vladyslav (My University, 2021)
A promising raw material for the production of meat products is hemp seeds - one of the best sources of easily digestible vegetable protein; phytonutrients that maintain the normal condition of tissues, blood vessels, skin cells and internal organs; polyunsaturated fatty acids; vitamins A, D and E and group B, calcium, sodium, iron and dietary fiber. Перспективною сировиною для виробництва м’ясних продуктів є насіння конопель – одне з найкращих джерел легкозасвоюваного рослинного білка; фітонциди, що підтримують нормальний стан тканин, судин, клітин шкіри та внутрішніх органів; поліненасичені жирні кислоти; вітаміни A, D і E і групи B, кальцій, натрій, залізо і харчові волокна.
Keywords: кафедра технології м’яса і м’ясних продуктів; seed; vegetable protein; meat; flour; oil; micronutrients; насіння; рослинний білок; мат; борошно; олія; мікроелементи